Sustainable Consumer Behavior - Gerrit Antonides (Ed.) (MDPI - Multidisciplinary Digital Publishing Institute, 2017)
Sustainability may be achieved through many different agents and institutions in society, including governments, new technologies, industries, and markets. In addition to these agents, consumers and households play a crucial role in the adoption of sustainable products and technologies. Additionally, households are responsible for substantial proportions of energy use and waste. In the European Union, the end use of total energy by households was about 25% in 2014 (Eurostat, 2016). Additionally, households generated 8% of total waste in the EU in 2012 (Eurostat, 2015). Moreover, ethical aspects of consumption are becoming more and more important. In order to gain understanding of sustainable consumer and household behavior, Sustainability has devoted an entire Special Issue to this topic. The Special Issue includes studies focusing on macro- and meso-issues, such as political parties' positions, nationality, social dilemmas and collective consumer efforts. Others studies focus on micro-issues of consumer behaviour, such as consumer segmentation, consumer perceptions, opinions, and intentions. The studies employ a variety of methods, including surveys, experiments, eye tracking, and contingent valuation. The collection of studies provide a balanced overview of consumer research in the field of sustainability.